The Correlation Between Airborne Pollen and Sensitization in Children with Respiratory Allergic Diseases: A Cross-Sectional Study - Xu L; Dai Y; Luo W; Jiang W; Tan Q; Lu Y; Huang Z; Gu W; Li P; Wang P; Huang L; Sun H; et al. (Journal of Asthma and Allergy)
Lina Xu,1,* Yinfang Dai,1,* Wenting Luo,2,* Wujun Jiang,1 Qianlei Tan,1 Yanhong Lu,1 Zhifeng Huang,2 Wenjing Gu,1 Pengyun Li,1 Pengli Wang,1 Li Huang,1 Huiquan Sun,1 Chuangli Hao,1 Baoqing Sun2 1Department of Respiratory Medicine, Children’s Hospital of Soochow University, Suzhou, Jiangsu, People’s Republic of China; 2Department of Allergy and Clinical Immunology, State Key Laboratory of Respiratory Disease, National Clinical Research Center for Respiratory Disease, Guangzhou Institute of Respiratory Health, First Affiliated Hospital, Guangzhou Medical University, Guangzhou, Guangdong, People’s Republic of China*These authors contributed equally to this workCorrespondence: Chuangli Hao, Department of Respiratory Medicine, Children’s Hospital of Soochow University, Suzhou, 215003, People’s Republic of China, Email hcl_md@sina.com Baoqing Sun, Department of Allergy and Clinical Immunology, State Key Laboratory of Respiratory Disease, National Clinical Research Center for Respiratory Disease, Guangzhou Institute of Respiratory Health, First Affiliated Hospital, Guangzhou Medical University, Guangzhou, Guangdong, 510120, People’s Republic of China, Email sunbaoqing@vip.163.comBackground: Pollen is a significant contributor to respiratory allergies worldwide, underscoring the importance of understanding its association with childhood sensitization to enhance clinical management.Objective: This study focuses on investigating the prevalence of various airborne pollens and their correlation with clinical characteristics of childhood respiratory allergic diseases in southeastern China.Methods: From November 2020 to October 2021, this research employed Durham monitoring samplers to collect airborne pollen. Simultaneously, skin prick tests (SPTs) were performed on children with respiratory allergic conditions at the Children’s Hospital of Soochow University and standardised questionnaires are also administered to assess children’s symptoms.Results: Over the course of November 2020 to October 2021, the study identified more than 36 pollen species. Notably, the spring season (March to May) exhibited the highest pollen concentrations, with Broussonetia accounting for 30.04% and Pinus for 26.38%. Similarly, the autumn months (September to October) saw prominent taxa like Humulus scandens (47.55%) and Gramineae (35.93%). Among the patients, a significant 92.7% exhibited positive reactions, with 81.7% showing sensitization to house dust mites (HMD), 17.8% to pollen, and 3.7% to Cockroach. Noteworthy the five most common pollens were observed for Bermuda (6.0%), Elm pollen (6.0%), Birch pollen (4.6%), and Mugwort (4.6%). The study indicated a substantial multisensitized ratio among pollen-sensitized patients in comparison to non-pollen-sensitized ones (97.4% vs 1.6%, P < 0.001). Moreover, weekly total airborne pollen concentrations showed positive correlations with weekly admissions due to allergic rhinitis(AR)(r=0.642, P < 0.001), bronchial asthma (BA) (r= 0.472, P< 0.001), and the coexistence of AR and BA (r=0.485, P < 0.001).Conclusion: The findings found that there were two peaks of pollen count in a year during March-May and September-October. The findings emphasize the critical role of specific airborne pollens in driving sensitization and exacerbating respiratory allergic diseases in children.Keywords: pollen, respiratory allergic diseases, China